MORPHOLOGICAL AWARENESS AND ITS CORRELATION WITH EFL STUDENTS’ READING COMPREHENSION IN SECONDARY SCHOOL - Millatuz Zakiyah; Suvi Akhiriyah (Journal of English Language Learning, 2022)
Morphological awareness, as one of the mediators which gives impact, plays an important role in achieving successful reading comprehension. It is believed that morphological awareness contributes to enhance students' performances by analyzing the word structures. Students are required to improve their skills in manipulating and interpreting complex words presented in a text. This study then, investigates the students’ level of morphological awareness and its relationship with their reading comprehension. It was carried out with a group of 55 second-grade EFL students from one of Gresik's senior high schools in East Java. The data were collected through reading comprehension test and morphological awareness test. The results indicates that students’ level of morphological awareness are varied (5 students = Excellent, 21 students = Good, 18 students = Mediocre, 10 students = Poor, and 1 student = Very Poor). In addition, the results show students’ morphological awareness has no link with their reading comprehension (p-value= .357, > .05).